Pennsylvania's Tobacco Education Project - Medical School Module - Sarah Evers-Casey; Frank Leone; Linda Kanzleiter (Association of American Medical Colleges, 2009)
Abstract The Pennsylvania Continuum of Tobacco Education Project was developed in order to create a generalizable method of improving students' knowledge, attitudes, and behaviors related to tobacco-use treatment. This module includes pertinent information and resources necessary to plan, train, implement, and evaluate a comprehensive tobacco education curriculum in medical schools. The educational methods and evaluation strategies were successfully implemented in three independent institutions across Pennsylvania. Planning: Worksheets allowed planners to share ideas, improve communication, anticipate inherent obstacles, and assist in developing plans for overcoming those obstacles in all three institutions. Training: Standardized patient (SP) training materials were used to help standardize the students' SP experience by providing a consistent point of reference. We were able to develop a cadre of SPs, each familiar with multiple scenarios, helping to overcome difficulties with SP availability and turnover over time. Evaluation: Factor analysis of the Confidential Tobacco Survey responses in a validation sample of third-year medical students yielded five independent factors with eigenvalues greater than 1, which accounted for 75% of the total variance. The first and largest factor (eigenvalue 7.3, 37% of variance) included six items related to students' self-assessment of knowledge and skills related to tobacco cessation (e.g., "I am comfortable prescribing medications that help in cessation"). Other factors related to students' perceptions regarding tobacco advertising, the utility of nicotine replacement therapy, the prospects for counseling patients in an ambulatory setting, and students' level of frustration with smokers who choose not to quit. As an intermediate measure of the effectiveness of our educational program, we monitored change in the rate of students' self-reported key behaviors over time using the Patient Encounter Log System (PELS). Over a 2-year period, students reported data for 85,728 encounters with adult and adolescent patients during the study period, of which 62,418 included a clinical history. Of the encounters with a clinical history, 37,023 (59%) included documentation that a smoking history had been obtained. The highest rate of collecting the smoking history (86%) was seen during the medicine clerkship. The lowest rates were reported in pediatrics (29%) and surgery (25%). PELS remained responsive across time, rotation type, and location, reflecting anticipated differences between primary versus tertiary care, community versus university settings, and pre- versus posttraining periods. Most medical school educators place a high priority on tobacco-use treatment instruction. However, schools are less likely to have a well-developed educational strategy, relying instead on the varied interests of faculty to "piecemeal" instruction. An organized approach to structuring tobacco-use instruction ensures a complete exposure over the course of 4 years and allows educators to isolate and modify approaches based on evaluated results. In addition, clinical skills training focused on important knowledge, attitudes, and skills related to tobacco-use treatment can be successfully accomplished by splitting up targeted outcomes across several scenarios, typical of the clerkship experience. Alternating outpatient and inpatient contexts allows students to explore ways of overcoming several predictable obstacles.